Visually guided step descent in children with Williams syndrome. - Cowie, D; Braddick, O; Atkinson, J (2012)
Individuals with Williams syndrome (WS) have impairments in visuospatial tasks and in manual visuomotor control, consistent with parietal and cerebellar abnormalities. Here we examined whether individuals with WS also have difficulties in visually controlling whole-body movements. We investigated visual control of stepping down at a change of level in children with WS (5-16-year-olds), who descended a single step while their movement was kinematically recorded. On each trial step height was set unpredictably, so that visual information was necessary to perceive the step depth and position the legs appropriately before landing. Kinematic measures established that children with WS did not use visual information to slow the leg at an appropriate point during the step. This pattern contrasts with that observed in typically developing 3- and 4-year-old children, implying severe impairment in whole-body visuomotor control in WS. For children with WS, performance was not significantly predicted by low-level visual or balance problems, but improved significantly with verbal age. The results suggest some plasticity and development in WS whole-body control. These data clearly show that visuospatial and visuomotor deficits in WS extend to the locomotor domain. Taken together with evidence for parietal and cerebellar abnormalities in WS, these results also provide new evidence for the role of these circuits in the visual control of whole-body movement.